Synchrotron X-ray Radiography and Tomography of Vanadium Redox Flow Batteries—Cell Design, Electrolyte Flow Geometry, and Gas Bubble Formation - Eifert, László; Bevilacqua, Nico; Köble, Kerstin; Fahy, Kieran; Xiao, Liusheng; Li, Min; Duan, Kangjun; Bazylak, Aimy; Sui, Pang Chieh; Zeis, Roswitha (Chemsuschem, 2020)
The wetting behavior and affinity to side reactions of carbon-based electrodes in vanadium redox flow batteries (VRFBs) are highly dependent on the physical and chemical surface structures of the material, as well as on the cell design itself. To investigate these properties, a new cell design was proposed to facilitate synchrotron X-ray imaging. Three different flow geometries were studied to understand the impact on the flow dynamics, and the formation of hydrogen bubbles. By electrolyte injection experiments, it was shown that the maximum saturation of carbon felt was achieved by a flat flow field after the first injection and by a serpentine flow field after continuous flow. Furthermore, the average saturation of the carbon felt was correlated to the cyclic voltammetry current response, and the hydrogen gas evolution was visualized in 3D by X-ray tomography. The capabilities of this cell design and experiments were outlined, which are essential for the evaluation and optimization of cell components of VRFBs.
CRIS-Team Scopus Importer:2023-08-01
Keywords: carbon electrodes; electrolyte distribution; flow geometries; synchrotron X-ray imaging; vanadium redox flow cell